Color-color diagrams in near infrared: (J-H)/(H-K). II. - Gyulbudaghian, A. L.; Baloian, N.; Sanchez, I. A.
In the paper the color-color diagrams (J-H)/(H-K) for all stars with visible magnitudes B<11m (for which in the existing catalogs the magnitudes of J, H, K, and also their spectral types and luminosity classes are given) are presented. In the preceding paper the data for luminosity classes I, Ia, Ib, II and III were given. In this paper the data on luminosity classes IV (sub giants) and V (main sequence stars) are given. Among the diagrams of luminosity classes the most interesting are the diagrams for GII and GIV stars, each of these diagrams have two centers of concentrations. For stars of spectral class M the minimal amount of stars is at luminosity class IV, the maximal –at class III, which is not so for other spectral classes: for other classes the maximal amount is at class V. There is a tendency (seen in all diagrams)of increasing of the values of J-H and H-K along the sequence O-B-A-F-G-K-M.
Keywords: Astronomy